Kontribusi Kemampuan Komunikasi dan Dukungan Sosial terhadap Kinerja Dosen dalam Pembelajaran di Poltekkes Surakarta - Pudjiastuti, Sri Surini; , Prof. Dr. Sutama, M.Pd; , Dr. Suyatmini, M.Si (2015)
Sri Surini Pudjiastuti. Q100130065. The Contribution of the communication skills and social support Towards the performance of Lecturers In learning at the Poltekkes of Surakarta. Thesis. Management Education Administration. Graduate School. Muhammadiyah University of Surakarta. 2015. This study aims to examine the contribution of communication skills and social support either simultaneously or partially on the performance of the lecturers in learning at the Poltekkes of Surakarta. This research is quantitative research. The selected research design is correlational research design, where correlational study aimed to see how big the association between several variables to one another. Based on the aim of this study include the type of predictive research. Through correlational studies, but can be sought correlations between variables can also be calculated regression, so predictable impact or contribution of two variables against one another variable. Implementation of research at Poltekkes of Surakarta. When the study was conducted over six months, starting in November 2014 to April 2015. The study population was lecturer at the Poltekkes of Surakarta, totaling 143 people. The sample used in the study a number of 105 respondents. The sampling technique using random sampling. The technique of collecting data using questionnaires, documentation and interviews. Data were analyzed using classic assumption test, correlation analysis, multiple linear regression analysis, F test, t test and the coefficient of determination. Based on the results of data analysis and discussion, we concluded that: (1) there is a significant contribution communications capabilities Lecturer and social support simultaneously on the performance of lecturers in learning, means the better the communication skills of lecturers and social support were obtained by the performance of lecturers in learning will also increase , so the hypothesis can be accepted, (2) there is a positive contribution and significant correlation between communication skills Lecturer partially on the performance of lecturers in learning, means the better communication skills Lecturer then the performance of lecturers in the learning will also increase, so the hypothesis, can received, (3) there is a positive and significant contribution between social support partially on the performance of lecturers in the learning, means the better social support obtained lecturer then lecturer in learning performance will also increase, so the hypothesis can be accepted.